Life cycle assessment of a novel electrocatalytic process for the production of bulk chemical ethylene oxide from biogenic CO2 - Rodin, Valerie; Zeilerbauer, Lukas; Lindorfer, Johannes; Paulik, Christian; Finger, David (Frontiers in Sustainability, 2022)
Carbon capture and utilization (CCU) technologies support future energy and climate transition goals by recycling carbon dioxide (CO2) emissions. The use of biogenic CO2 from renewable sources, is an avenue for the production of fully renewable products. Fossil-based materials can potentially be replaced in the long term while allowing for the use of so called “waste” streams. To foster the development of a circular economy more insights need to be gained on the life cycle impact of CCU technologies. This study analyzed a CCU process chain, with focus on the utilization of volatile renewable electricity and biogenic CO2. We performed a cradle-to-gate life cycle assessment, evaluating various environmental impact categories (CML 2001 methodology) and primary energy demand (PED) with GaBi LCA software by sphera®. The targeted olefin is ethylene oxide (C2H4O), which is a crucial intermediate chemical for the production of various synthetic materials, such as polyethylene terephthalate (PET). As functional unit, 1 kg ethylene oxide was chosen. In the novel process at first ethylene (C2H4) and hydrogen peroxide (H2O2) are produced from water and CO2 via an electrocatalytic process (Power-to-X process). In a second step, the two intermediates are synthesized to ethylene oxide. The theoretical implementation of a medium-scale process under average European conditions was considered in twelve scenarios that differed in energy supply and CO2 source. Sensitivity analyses were conducted to evaluate the influence of the energy and resource efficiencies of the production steps. The process was compared to its fossil benchmark, an existing conventional EO production chain. Concerning the global warming potential (GWP), negative emissions of up to -0.5 kg CO2 eq./kg product were calculated under optimized process conditions regarding energy and conversion efficiency and using biogenic CO2. In contrast, the GWP exceeded the fossil benchmark when the European grid mix was applied. The PED of 87 MJ/kg product under optimized conditions is comparable to that of other Power-to-X processes, but is high compared to fossil-based ethylene oxide. Based on the results we conclude that the energy efficiency of the electrocatalytic cell and renewable energy as input are the main levers to achieve a low environmental impact.